2016
DOI: 10.1177/1468017315583172
|View full text |Cite
|
Sign up to set email alerts
|

Prepared enough to practise? Evaluating a study programme in social work

Abstract: Summary: Following the so-called Bologna reform in Luxembourg, 70 supervisors assessed the knowledge and skills of employees having qualified with a Bachelor's degree under the recently introduced curriculum in social work and pedagogy. The supervisors were solicited as part of quality assurance regarding the study programme and their assessments were gathered by means of a questionnaire. The University of Luxembourg funded the study.Findings: The newly qualified practitioners were evaluated as adequately trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In order to ensure their anonymity, they were instructed to hand in the questionnaire without recording either name or student registration number on it. They were accurately informed that their effort would provide helpful input to the overall evaluation of the study programme (see Engelberg & Limbach-Reich, 2012, 2015. All students opted to participate and completed the questionnaire in full.…”
Section: Respondentsmentioning
confidence: 99%
“…In order to ensure their anonymity, they were instructed to hand in the questionnaire without recording either name or student registration number on it. They were accurately informed that their effort would provide helpful input to the overall evaluation of the study programme (see Engelberg & Limbach-Reich, 2012, 2015. All students opted to participate and completed the questionnaire in full.…”
Section: Respondentsmentioning
confidence: 99%
“…Due to the complexity of the role of the practice teacher and the centrality of them to the education of social care students the aim of the research reported here was to explore similarities and differences in how practice teachers in social care education view their role and behaviours they prioritised. Due to some similarities between social work and social care work (Engelberg & Limbach-Reich, 2015), as well as the lack of research specific to social care practice, the literature reviewed includes that in relation to social work. …”
mentioning
confidence: 99%